Developmental dynamics is revealed in the early Cambrian arthropod Chuandianella ovata - Cong Liu; Dongjing Fu; Xingliang Zhang (iScience, 2022)
Summary: Segmentation and tagmatization have contributed to the preeminent success of arthropods since their first appearance in the Cambrian. However, the exact mechanism of segmentogenesis is still insufficiently known in living and extinct groups. Here, we describe the postembryonic development of a Waptiid arthropod Chuandianella ovata from the early Cambrian Chengjiang biota, South China. The new data illuminate a complex dynamic pattern of anamorphosis and epimorphosis, and a three-step process of segmentogenesis, i.e., the elongation of the terminal segment, delineation of an incipient segment, and full separation of a new segment. Compensatory growth is accomplished by rapid growth of new segments and/or generation of additional segments, which results in the trimorphism of the posterior tagma. Such complex developmental dynamics has rarely been known in the arthropod fossil record and its presence in early history helps to understand the rapid diversification of arthropods in the early Cambrian.